Rheumatoid Arthritis in Latin Americans Enriched for Amerindian Ancestry Is Associated With Loci in Chromosomes 1, 12, and 13, and the HLA Class II Region. Issue 6 (30th May 2013) - Herráez, David López; Martínez‐Bueno, Manuel; Riba, Laura; de la Torre, Ignacio García; Sacnún, Mónica; Goñi, Mario; Berbotto, Guillermo A.; Paira, Sergio; Musuruana, Jorge Luis; Graf, César E.; Alvarellos, Alejandro J.; Messina, Osvaldo D.; et al.
Abstract : Objective: To identify susceptibility loci for rheumatoid arthritis (RA) in Latin American individuals with admixed European and Amerindian genetic ancestry. Methods: Genotyping was performed in 1, 475 patients with RA and 1, 213 control subjects, using a customized BeadArray containing 196, 524 markers covering loci previously associated with various autoimmune diseases. Principal components analysis (EigenSoft package) and Structure software were used to identify outliers and define the population substructure. REAP software was used to define cryptic relatedness and duplicates, and genetic association analyses were conducted using Plink statistical software. Results: A strong genetic association between RA and the major histocompatibility complex region was observed, localized within BTNL2/DRA–DQB1– DQA2 ( P = 7.6 × 10 −10 ), with 3 independent effects. We identified an association in the PLCH2‐HES5‐TNFRSF14‐MMEL1 region of chromosome 1 ( P = 9.77 × 10 −6 ), which was previously reported in Europeans, Asians, and Native Canadians. We identified one novel putative association in ENOX1 on chromosome 13 ( P = 3.24 × 10 −7 ). Previously reported associations were observed in the current study, including PTPN22, SPRED2, STAT4, IRF5, CCL21, and IL2RA, although the significance was relatively moderate. Adjustment for Amerindian ancestry improved the association of a novel locus in chromosome 12 at C12orf30 ( NAA25 ) ( P = 3.9 × 10 −6 ). Associations with the HLA region, SPRED2, and PTPN22 improved in individuals positive for anti–cyclic citrullinated peptide antibodies. Conclusion: Our data define, for the first time, the contribution of Amerindian ancestry to the genetic architecture of RA in an admixed Latin American population by confirming the role of the HLA region and supporting the association with a locus in chromosome 1. In addition, we provide data for novel putative loci in chromosomes 12 and 13.